Echocardiographic Evaluation of Diastolic Dysfunction in Patients with Subclinical Hypothyroidism & the effect of L-Thyroxine treatment: A hospital based study - Karki, Prahlad; Pandey, Ila; Bhandary, Sangita; Lamsal, Madhab; Shrestha, Nikesh Raj (Nepalese Heart Journal, 2014)
Background & Aims: Diastolic dysfunction is the common condition with Subclinical Hypothyroidism and is reversible in many cases after treatment. We aimed to investigate the response of diastolic dysfunction to thyroid hormone replacement therapy in patients of Subclinical Hypothyroidism. Methods: Forty newly diagnosed cases of Subclinical Hypothyroidism (38 females and 2 males) and age more than 18 years were included. Diagnosis was made on the basis of history, clinical examination and thyroid function tests. Echocardiography was performed in all and was repeated after 4-6 months in those who had diastolic dysfunction. Distribution of Diastolic dysfunction among the involved cases and their response to treatment with L-thyroxine were studied. Results: The diastolic dysfunction was found in 15 (37.5%) and pericardial effusion (PE) in five (12.5%) patients. Fourteen of them had impaired relaxation abnormality and only one patient had pseudonormal pattern. With replacement therapy, 13 reverted back to the normal whereas one having grade 2 diastolic dysfunction (pseudonormal pattern) reverted to grade 1. One patient who had grade 1 diastolic dysfunction (impaired relaxation) did not improve. Pericardial effusion subsided in all 5 cases. Conclusions: Echocardiography may be a useful tool for monitoring the response of diastolic dysfunction to thyroid hormone replacement therapy in patients with Subclinical Hypothyroidism. Our findings suggest that Thyroid Hormone Replacement Therapy may reverse diastolic dysfunction in Subclinical Hypothyroidism. DOI: http://dx.doi.org/10.3126/njh.v11i1.10979 Nepalese Heart Journal 2014;11(1): 33-38